Faktor-Faktor yang Berhubungan dengan Kekurangan Energi Kronik (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Putri Ayu Kota Jambi - Leony Lorenza; Usi Lanita; Silvia Mawarti Perdana; Asparian, Asparian; Sri Astuti Siregar (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Chronic Energy Deficiency (CED) is a manifestation of malnutrition characterized by an inadequate energy intake over a prolonged period in pregnant women, resulting in adverse health outcomes due to a relative or absolute deficiency of one or more essential nutrients. The 2023 SKI results indicate that malnutrition among pregnant women remains a problem, with nearly 3 out of 10 pregnant women experiencing anemia and 17% at risk of CED. According to data from the Jambi City Health Office, Putri Ayu Public Health Center (Puskesmas Putri Ayu) has the highest number of CED cases, with 67 affected pregnant women. The main objective of this study is to explain the underlying factors contributing to the high prevalence of Chronic Energy Deficiency (CED) and to inform the development of evidence-based health interventions aimed at reducing this condition. This study employed a quantitative research method with a case-control design. The sampling technique used was purposive total sampling, involving 78 pregnant women in the Putri Ayu Public Health Center area, Jambi City. Data collection was conducted in October 2024, using a questionnaire as the research instrument. Data were analyzed using the chi-square test. The results showed a significant relationship between CED and parity (p=0.034), anemia (p=0.013), attitude (p=0.000), and the role of health workers (p=0.000). No significant relationship was found between CED and age (p=1.000), pregnancy spacing (p=0.615), and knowledge (p=0.359) in pregnant women. The findings indicate that parity, anemia, attitude, and the role of health workers are significantly associated with the occurrence of CED in pregnant women, while age, pregnancy spacing, and knowledge are not significantly associated.